Two-Loop Six Gluon All-Plus Helicity Amplitude - David Dunbar (Physical Review Letters, 2016)
We present an analytic expression for the six-point all-plus helicity amplitude in QCD at two-loops. We compute the rational terms in a compact analytic form organised by their singularity structure.